“God, I Hope It Doesn’t Fade Out”: Team Member Perspectives on the Future of Veterans Treatment Courts - Socia, Kelly M. (Victims & offenders, 2024)
Despite their rapid spread over the last 15 years, little research has explored the perceptions of Veterans Treatment Courts (VTCs) team members regarding the viability and longevity of VTCs. The present qualitative study explores the perceptions of 145 VTC team members from 20 VTCs around the United States regarding the future of their own VTC and VTCs in general. Our analysis revealed four overarching themes about team members’ expectations and hopes for VTCs in the future: the need for continued funding and increased resources; desires to expand participation in VTCs; hope and uncertainty about the future of VTCs; and depending on specific people to ensure the future of VTCs. While interviewees in general felt quite hopeful and optimistic that VTCs would continue to exist and may even expand, there was unease about exactly how this would occur. These concerns included securing stable funding sources, maintaining “buy in” from key individuals, and resource needs for expanding the participation and eligibility criteria of VTCs. Given the important role that VTCs can play in effectively supporting justice-involved veterans, and offering more benefits compared to a traditional justice-system response, it seems vital to ensure that VTCs are able to continue operating in the future.